Identification of Claudin 6-specific HLA class I- and HLA class II-restricted T cell receptors for cellular immunotherapy in ovarian cancer. (31st December 2022) - Matsuzaki, Junko; Lele, Shashikant; Odunsi, Kunle; Tsuji, Takemasa
ABSTRACT: Adoptive cell therapy (ACT) is one of promising immunotherapies for cancer patients by providing a large amount of cancer antigen-specific effector T cells that can be manufactured rapidly by ex vivo gene engineering. To provide antigen-specificity to patients' autologous T cells in a short-term culture, T-cell receptors (TCRs) or chimeric antigen receptors (CARs) are transduced to bulk T cells. Because of intra- and inter-tumoral heterogeneity in tumor antigen expression, a repertoire of TCR or CAR genes targeting a wide range of tumor antigens are required for a broad and effective treatment by ACT. Here, we characterized immunogenicity of claudin 6 (CLDN6) in ovarian cancer patients and identified specific TCR genes from CD8 + and CD4 + T cells. CLDN6 protein was frequently expressed on EpCAM + ovarian cancer cells but not CD45 + lymphocytes in tumor ascites of ovarian cancer patients. Spontaneous CLDN6-specific CD4 + and CD8 + T-cell response was detected in peripheral blood mononuclear cells (PBMCs) from 1 out of 17 ovarian cancer patients. HLA-A*02:01 (A2) and DR*04:04 (DR4)-restricted TCR genes were isolated from CLDN6-specific CD8 + and CD4 + T cells, respectively. T cells that were engineered with A2-restricted TCR gene recognized and killed A2 + CLDN6 + cancer cells. DR4-restricted TCR-transduced T cells directly recognized DR4 + CLDN6 + -overexpressed cancer cells. Our results demonstrate that these CLDN6-specific TCR genes are useful as therapeutic genes for ACT to patients with ovarian and other solid tumors expressing CLDN6.